2021
DOI: 10.3389/fphar.2021.602816
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rhubarb for the Treatment of Diabetic Nephropathy in Animals: A Systematic Review and Meta-analysis

Abstract: Background: Rhubarb, also known as Da Huang, is a traditional Chinese medicine, and it was often used as a laxative in the past. Recently, multiple studies have applied rhubarb to treat diabetic nephropathy (DN). Anthraquinones, including emodin and rhein, have been extracted from rhubarb and used to explore the effective components and possible mechanisms of rhubarb for DN. Evaluating the efficacy of rhubarb may provide a scientific reference for the clinical application of rhubarb for the treatment of DN.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The initial search yielded 740 relevant records (145 from CBM, 271 from CNKI, 151 from VIP and 173 from Wanfang). NoteExpress software was used for de-weighting, and the exclusion of ineligible papers was carried out according to the pre-designed de-weighting criteria, and a total of 34 papers were finally identified for inclusion ( Yokozawa et al, 1986 ; Duan, 2005 ; Gao, 2005 ; Zhang, 2005 ; Chang, 2006 ; Chen and Diao, 2008 ; Liu and Feng, 2008 ; Sun, 2008 ; Yuan, 2008 ; Cao, 2009 ; Chen, 2009 ; Dan, 2009 ; Rai, 2009 ; Xue, 2009 ; Hang, 2010 ; Jing, 2010 ; Liu, 2010 ; Liu and Li, 2012 ; Ma et al, 2012 ; Zeng, 2012 ; Han, 2013 ; Wang and Sun, 2015 ; Yan, 2015 ; Qin, 2016 ; Williams and Heller, 2016 ; Li et al, 2017 ; Zhang et al, 2018 ; Xue et al, 2019 ; Yu, 2019 ; Gong et al, 2020 ; Jin, 2020 ; Yang, 2020 ; Zeng et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search yielded 740 relevant records (145 from CBM, 271 from CNKI, 151 from VIP and 173 from Wanfang). NoteExpress software was used for de-weighting, and the exclusion of ineligible papers was carried out according to the pre-designed de-weighting criteria, and a total of 34 papers were finally identified for inclusion ( Yokozawa et al, 1986 ; Duan, 2005 ; Gao, 2005 ; Zhang, 2005 ; Chang, 2006 ; Chen and Diao, 2008 ; Liu and Feng, 2008 ; Sun, 2008 ; Yuan, 2008 ; Cao, 2009 ; Chen, 2009 ; Dan, 2009 ; Rai, 2009 ; Xue, 2009 ; Hang, 2010 ; Jing, 2010 ; Liu, 2010 ; Liu and Li, 2012 ; Ma et al, 2012 ; Zeng, 2012 ; Han, 2013 ; Wang and Sun, 2015 ; Yan, 2015 ; Qin, 2016 ; Williams and Heller, 2016 ; Li et al, 2017 ; Zhang et al, 2018 ; Xue et al, 2019 ; Yu, 2019 ; Gong et al, 2020 ; Jin, 2020 ; Yang, 2020 ; Zeng et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…ex Regel ) Balf ., ( The Angiosperm Phylogeny Group et al, 2016 ). Rhubarb has been applied in the treatment of CRF in recent years with remarkable clinical efficacy ( Zeng et al, 2021 ). Previous studies have suggested that rhubarb treats chronic renal failure mainly as a laxative, causing uremic toxins to be excreted from the bowels via the intestines ( Yokozawa et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the bioactive fraction of ethyl acetate extract of SKI, we identified three anthraquinones including chrysophanol, emodin, and rhein that were major and bioactive components of Rheum officinale , which has been demonstrated to improve CKD and renal fibrosis ( Wang et al, 2012 ; Zhang et al, 2018 ; Zeng et al, 2021 ). Compared with chrysophanol and emodin, rhein showed a strong inhibitory effect on renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…was observed in the last three months by curcumin supplementation [94]. Rhubarb is one of the most important natural products and is usually used for treating renal diseases [95][96][97][98]. Treatment with rhubarb enema could decrease the levels of trimethylamine N-oxide and trimethylamine in serum, suppress the expression of interleukin-6, tumour necrosis factor α and interferon-γ and mitigate tubular atrophy, inflammatory cell infiltration and tubulointerstitial fibrosis in the 5/6 nephrectomized rats [82].…”
Section: Intervention Strategies Through Regulating Gut Microbiota In...mentioning
confidence: 99%